Compliance como ferramenta de mitigação e prevenção da fraude organizacional - Santos, Renato de Almeida dos (2011)
Fraud is a systemic phenomenom that provokes ruptures in the social tissue and massive damages to private and governmental organizations, and, ultimately, to the citizens. The literature about this phenomenom is still polemic in the matter of concepts and indicators. The possible indicators are necessarily indirect, and must be handled with caution. To deal with the theoretical and measuring difficulties, this work proposes to study the fraud phenomenom in the dimension of the individual's moral perception, with the goal of stimulating the development of compliance programs that aim to mitigate the risk and control fraud in organizations, through formal instruments and culture related actions. The purpose of this work is to deepen the knowledge about the factors that influence the individual's decision to commit fraud in private organizations, as well as to evaluate the results of the implementation of compliance programs on the moral perception of the individuals from these organizations. The theoretical referential is centered in a conceptual review about fraud, having as theoretical base the Fraud Triangle (CRESSEY, 1953) and compliance tools. The research is based in secondary data provided by ICTS Global, an international company specialized in risk reduction. The data consists in a non-probability convenience sampling, conducted between 2004 and 2008, with employees and candidates of 74 private companies in Brazil. The final number of individuals researched was 7,574. Because it was an exploratory type of research, many different statistic tests were made, based on nine indicators of moral perception from the Analysis of Adherence to Ethics index (AAE). The data obtained by the research indicates that there is a fragility of the ethical principles in the root of the fraud, although the context (or the situational pressure) and the opportunity are combined in the production of acts of corruption or in conformity. It also indicates that the compliance tools do not hinder the problematic of fraud, but its inexistence strengthens this phenomenom